Utilitarian Motivation and Promotions on Purchase Decisions: Perceived Value as a Mediating Variable Among TikTok Shop Users in Indonesia - Salsabila, Naila; Mansyuri, M. Ikhwan; Ramadhan, Risca Ariska (Advances in Management & Financial Reporting, 2026)
Purpose: This study examines the effects of utilitarian motivation and promotions on purchase decisions and tests the mediating role of perceived value among TikTok Shop social commerce users in Indonesia. Research Method: This research used an explanatory quantitative design. Data were collected from 91 STIE Yapis Dompu students who actively use TikTok Shop. The sample size was determined using the rule of 5–10 times the number of observed indicators. The variables analyzed were utilitarian motivation, promotions, perceived value, and purchase decisions. Data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS v3. Results and Discussion: The findings show that utilitarian motivation and promotions have positive and significant effects on perceived value and purchase decisions. Perceived value also positively and significantly affects purchase decisions. However, perceived value does not significantly mediate the effects of utilitarian motivation and promotions on purchase decisions, although the indirect effects are positive. This indicates that TikTok Shop users tend to respond directly to practical benefits and promotional offers without extensive evaluation of value. Implications: TikTok Shop businesses should emphasize promotional strategies that encourage quick purchases, such as flash sales and live discounts, while improving transaction convenience.